Probing the multipolar structure of Myers-Perry black holes with scattering amplitudes - Massimo Bianchi; Claudio Gambino; Fabio Riccioni; Vincenzo Zevola (Journal of High Energy Physics)
Abstract We discuss the scattering of massive scalar probes off Myers-Perry black holes in the Kerr-Schild gauge. Extending the analysis performed recently for Kerr(-Newman) black holes, we show that the Kerr-Schild gauge allows to write down the tree-level scattering amplitude for Myers-Perry black holes in analytic form. For generic values of the angular momenta, Myers-Perry solutions have a richer multipolar structure compared to their four-dimensional counterparts, because they are characterized by the presence of stress multipoles, together with the more familiar mass and current multipoles. By focusing on the five-dimensional case, we derive the leading eikonal phase from the scattering amplitude and we give an explicit expression for two limiting scenari, namely when the two angular momenta are the same, so that the mass multipoles vanish but still the solution has a non-vanishing stress quadrupole and a current dipole, and when one of the two angular momenta is zero, and correspondingly the stress multipoles vanish similar to the Kerr case.